Análise genética da população de Thrichomys apereoides (RODENTIA, Echimyidae) no norte de Minas Gerais - Aparecida Pilar e Silva (2011)
The genetic diversity presented in a population of wild rodent Thrichomys apereoides from the northern of Minas was analyzed through the mitochondrial marker of control region, D loop. The individuals came from three different collection points. There were found nineteen haplotypes which were distributed in three points, where the colletions were made. The population showed high haplotype diversity and low nucleotide diversity as observed in some studies of other rodents families. Tests analyzes of neutrality pointed to a population which is in recent demographic expansion, which cannot be observed through the pairwise differences in the frequencies of nucleotides.